2009
DOI: 10.1097/yct.0b013e3181794690
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy Practice in Poland

Abstract: The rate of ECT use in Poland is among the lowest in the Central-East European region, which raises the possibility that many patients who otherwise would greatly benefit from ECT do not receive this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 19 publications
2
28
1
Order By: Relevance
“…The limited accessibility of ECT for these special patient populations is a cause for concern because it precludes the access to an effective and safe treatment modality. present in Europe between Denmark (Andersson and Bolwig 2002) and Poland (Gazdag et al 2009). Given the very similar historical, socio-cultural and political backgrounds of the three Baltic states, the differences are intriguing and might refl ect the infl uence of local factors like public attitude towards ECT or the views of individual department heads.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The limited accessibility of ECT for these special patient populations is a cause for concern because it precludes the access to an effective and safe treatment modality. present in Europe between Denmark (Andersson and Bolwig 2002) and Poland (Gazdag et al 2009). Given the very similar historical, socio-cultural and political backgrounds of the three Baltic states, the differences are intriguing and might refl ect the infl uence of local factors like public attitude towards ECT or the views of individual department heads.…”
Section: Discussionmentioning
confidence: 96%
“…While the use of electroconvulsive therapy (ECT) has been investigated in most Western European (Andersson and Bolwig 2002;Verwey et al 2005;Bertolin-Guill é n et al 2006;Sienaert et al 2006;Bickerton et al 2009;Schweder et al 2011;Loh et al 2012) and several Central/Eastern European countries (Gazdag et al 2004(Gazdag et al , 2009Dragasek et al 2008;Hranov et al 2012), nothing is known about its use in the Baltic states. These countries, Estonia, Latvia and Lithuania, which are located on the east coast of the Baltic Sea, were annexed by the Soviet Union between 1940 and 1991, and regained their independence in 1991.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…With 3.4 per 10 5 inhabitants treated with ECT, Germany is ahead of Austria, Hungary, Poland and Switzerland and Bulgaria at the lower end of the list of treatment frequencies per country (Gazdag et al 2004(Gazdag et al , 2009a. With 37.85 patients treated per 10 5 inhabitants (Chanpattana 2007), Australia heads the list of countries with the highest treatment frequencies.…”
Section: Frequency Of Ect Over Course Of Timementioning
confidence: 98%
“…Case et al (10) reported that the total number of hospitals offering ECT has been declining. In international settings, ECT utilization varies widely across regions, with utilization estimates ranging from 1.1 ECT patients per 100,000 people in Poland (11) to 41 ECT patients per 100,000 people in Sweden (12). The most recent utilization estimates for the procedure in the United States date to 1999 or earlier (13) and vary widely by region, ranging from eight ECT patients per 100,000 people in California (14) in 1995 to 42 ECT patients per 100,000 people in New England in the same year (15).…”
mentioning
confidence: 99%